LOWER EXTREMITY BALANCE IS IMPROVED AT TIME OF RETURN TO THROWING IN BASEBALL PLAYERS AFTER AN ULNAR COLLATERAL LIGAMENT RECONSTRUCTION WHEN COMPARED TO PRE‐OPERATIVE MEASUREMENTS - Hannon, Joseph (Sports Physical Therapy Section, 2014)
BACKGROUND: /Purpose: Lower extremity balance deficits have been shown to lead to altered kinematics and increased injury risk in lower extremity athletes. The purpose of this study was to compare lower extremity balance in baseball players with an ulnar collateral ligament (UCL) tear pre‐operatively and post‐operatively at the beginning of the pre‐return to throwing program stage of rehabilitation (3 months). METHODS: Thirty‐three competitive high school and collegiate male baseball players (18.5 ± 3.2) with a diagnosed UCL tear volunteered for the study. Of the 33 baseball players 29 were pitchers, 1 was a catcher, and 3 were infielders. Participants were seen pre‐operatively and at 3 months post operatively. This 3 month point was associated with a follow‐up visit to the orthopedic surgeon and subsequent release to begin the pre‐return to throwing mark for baseball players following their surgery. Following surgery, each participant followed a standard UCL protocol which included focused lower extremity balance and neuromuscular control exercises. Participants were tested for single leg balance using the Y‐Balance Test™ – Lower Quadrant (YBT‐LQ) on both their lead and stance limbs. YBT‐LQ composite scores were calculated for the stance and lead limbs pre‐ and post‐operatively and compared over time. Paired t‐tests were used to calculate differences between time 1 and time 2 (p < 0.05). RESULTS: Baseball players with diagnosed UCL tears demonstrated significant balance deficits on their stance (p < .001) and lead (p = .009) limbs prior to surgery compared to balance measures at the 3‐month follow up (Stance Pre‐Op = 89.4 ± 7.5%; Stance 3 Month = 94.9 ± 9.5%) (Lead Pre‐Op = 90.2 ± 6.7%; Lead 3 Month = 93.6 ± 7.2%). CONCLUSION: Based on the results of this study, lower extremity balance is altered in baseball players with UCL tears prior to surgery. Statistically significant improvements were seen and balance measures improved at the time of return to throwing. LEVEL OF EVIDENCE: Level 2b